Data from: Large frugivores matter: insights from network and seed dispersal effectiveness approaches - Naniwadekar, Rohit; Chaplod, Saniya; Datta, Aparajita; Rathore, Akanksha; Sridhar, Hari (Dryad, 2019)
1.While large avian frugivores are known to be key dispersers for
large‐seeded tree species, their role in community‐wide plant‐disperser
networks is still poorly known. Large avian frugivores are also among the
most threatened due to anthropogenic impacts. 2.We evaluated the role of
large avian frugivores in a plant‐disperser community by a) determining
whether the plant‐disperser community was modular, with a distinct
community of large frugivores (thereby highlighting their importance), b)
determining relative qualitative and quantitative roles played by
large‐bodied frugivores vis‐à‐vis other frugivores and c) determining
impacts of large‐bodied frugivore loss on the plant‐disperser community.
3.The study was carried at a tropical forest site in north‐east India
which is part of the Eastern Himalaya Biodiversity Hotspot. We collected
tree watch data (2055 h) from 46 tree species, which represented 85% of
tree species that are predominantly bird‐dispersed in the area. 4.We found
that the plant‐disperser community was modular, with a distinct module of
large‐seeded tree species and large frugivores. Intermediate‐sized
frugivores such as barbets and bulbuls were the most connected, while
large‐sized frugivores, such as hornbills and imperial‐pigeons were
moderately well‐connected. Qualitative and quantitative roles played by
different dispersers varied across the gradient of frugivore body size.
Hornbills, the largest avian frugivores, consumed a significantly greater
number of fruits and swallowed larger proportions of fruits compared to
other avian groups. In comparison to similar‐sized frugivores,
imperial‐pigeons fed on larger‐sized fruits, highlighting their importance
for dispersal of large‐seeded plants. Under simulated extinction
scenarios, larger extinction cascades weren't necessarily caused by
larger frugivores, however, extinctions of certain large‐bodied frugivores
(hornbills, imperial‐pigeons) caused extinction cascades. 5.Integrating
information from networks and seed dispersal effectiveness approaches
enabled a better understanding of large frugivore role in a
plant‐disperser community. While large‐bodied frugivores may not be
playing a central role in plant‐disperser communities, they are crucial as
seed dispersal service providers for large‐seeded plants. In conjunction
with the reported local extinctions of large frugivores like hornbills
from the south Asian region, this study's findings highlight the
irreplaceable quantitative and qualitative impacts that tropical plant
communities are likely to experience in the future.
RScript_JAE_Naniwadekar_etalThe R script that was used for data
analysisJAE_Naniwadekar_etal_species_codesContains details of codes
assigned to different plant and frugivore species across the different
data filesdat_species_accum_samplescontains data that was used to plot
frugivore species accumulation
curvesdat_pakke_weight_network_bird_dispcontains visitation rate data of
different frugivore species on different tree species that was used to
construct the plant-disperser networkdat_gw_fw_finalcontains data of gape
width of different frugivore species and the average diameter (width) of
fruit species eaten by themdat_correl_species_level_gwcontains data of
gape width of different frugivore species and degree, species strength,
betweenness centrality and closeness centrality measures for each of the
different species as extracted from each of the different frugivore
speciesdat_fruit_removalcontains data for the generalized linear mixed
effect models with negative binomial error structure to evaluate the
number of fruits swallowed per visit as a function of the gape width of
the frugivoredat_fruit_visit_ratecontains data for the linear mixed effect
models to evaluate the visitation rate of the different frugivore species
as a function of the gape width (body size) of the frugivoredata for seed
dispersal effectiveness landscapecontains data for constructing the seed
dispersal effectiveness
landscapem1.csvdat_prop_fruit_swallow_fruit_widthcontains data to
correlate the proportion of fruits swallowed as a function of fruit
widthdat_anova_modulescontains data to compare gape width and degree of
the different frugivore species that belong to different modules (A-E).
Modules were determined using modularity
analysis)dat_anova_modules_plantcontains data to compare fruit diameter
and degree of the differen plant species that belong to different modules
(A-E). Modules were determined using modularity
analysisdat_chi_test_seed_size_modulescontains data to compare the
relative proportion of small-, medium- and large-seeded tree species
across the different modulesdat_extinct_scmmatrix that contains data on
visitation rates of different frugivore species (in rows) on the different
tree species (in columnsdat_extinct_order_extinctioncontains data on gape
width, body length weight of the frugivores and proportion of fruits in
the diet of each of the frugivore species as obtained from Wilman et al.
(2015) that is useful for the stochastic co-extinction
modelsdat_vector_rplantscontains data on the dependence of each plant
species on animals for seed dispersal. Since all are animal-dispersed
plant species, they all take a value of 1
Keywords: Multi-trophic interactions; Hypsipetes leucocephalus; Eastern Himalaya; Treron; hornbills; barbets; Alophoixus flaveolus; Irena puella; Anthracoceros albirostris; Psilopogon lineatus; Modularity; Psilopogon asiaticus; Buceros bicornis; Ducula badia; Pycnonotus flaviventris; plant-disperser community; Rhyticeros undulatus